A review of the use of inhaled nitric oxide in the PICU at Red Cross Children's Hospital, 2011-2015: A retrospective cohort study - Padayachee, Sandhia (Department of Paediatrics and Child Health, 2020)
Background: Inhaled Nitric Oxide (iNO) functions as a selective pulmonary vasodilator. It is an expensive treatment that is often employed as rescue therapy for refractory hypoxaemia in acute respiratory distress syndrome (ARDS) and pulmonary hypertension (PHT) following cardiac surgery. Objectives: To describe the response to treatment with iNO. Secondary observations were deaths, comorbidities of the patients treated, lengths of treatment and admission, and the cost of treatment. Methods: A retrospective descriptive study of all patients treated with iNO in the Paediatric Intensive Care Unit (PICU) at Red Cross War Memorial Children’s Hospital (RCWMCH) from 2011- 2015. Results: A total of 140 patients were treated with iNO during this time period, 82 were for PHT following cardiac surgery, 53 for ARDS and 5 for PPHN. A response to treatment was observed in 64% of the cohort as a whole, 80% of those with PPHN, 67% of those with PHT post-cardiac surgery, and 64% of those with ARDS. A longer duration of ICU and hospital admission, and higher in hospital mortality (53%) was seen in the group with ARDS, in particular those with adenoviral infection (63%), when compared to patients treated for PHT (18%) and for PPHN (20%). There is no protocol in place guiding the use of iNO in our unit, and it was found that response to treatment was not being objectively measured and documented and that practise varied between clinicians. Conclusions: Considering the cost of treatment and lack of evidence to support beneficial effects of iNO therapy, its continued use in our resource poor setting should be guided by protocol.